The Effect of Carbohydrates on Physical Exercise and Sports Performance - Ms. Desh Kanwar; Dr. Vishnu Chaudhari (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Interest in the inspirations of food on the capability for physical activity is as old as manhood. From first times, certain foods were regarded as essential preparation for energetic physical activity. In a recent consent conference on food, nutrition and sports performance, carbohydrate having foods were identified as having the most significant impact on exercise performance. The nutritional importance of protein, as a fuel for exercise and as a contributor to strength development, has been over emphasized, whereas the fluid intake has been, by comparison, under played.